IoT-based flood disaster early detection system using hybrid fuzzy logic and neural networks - Muhammad Adib Kamali; Mochamad Nizar Palefi Ma’ady (Universitas Ahmad Dahlan, 2024)
A flood stands as one of the most common natural occurrences, often resulting in substantial financial losses to property and possessions, as well as affecting human lives adversely. Implementing measures to prevent such floods becomes crucial, offering inhabitants ample time to evacuate vulnerable areas before flood events occur. In addressing the flood issue, numerous scholars have put forth various solutions, such as the development of fuzzy system models and the es- tablishment of suitable infrastructure. However, when applying a fuzzy system, it often results in a loss of interpretability of the fuzzy rules. To address this issue effectively, we propose to reframe the optimization problem by incorpo- rating stage costs alongside the terminal cost. Results show the proposed model called hybrid fuzzy logic and neural networks (NNs) can mitigate the loss of interpretability. Results also show that the proposed method was employed in a flood early detection system aligned with integrating into Twitter social me- dia. The proposed concepts are validated through case studies, showcasing their effectiveness in tasks such as XOR-classification problems.